FERRETS - Wolf, Tiffany M. (Manual of Exotic Pet Practice, 2009)
This chapter familiarizes veterinarians with basic knowledge of ferret biology, medicine, surgery, and care. Ferrets have a long, slender body with short muscular legs, a long thin tail, small eyes, and short ears. The life span of the ferret is 5 to 8 years. Ferrets may be housed singly or in groups, inside or outside of a house. When kept outdoors, however, they must be protected from extreme weather. Ferrets have difficulty tolerating temperatures above 90°F or below 20°F, and appropriate precautions must be taken to prevent their exposure to these extremes. Ferrets are carnivorous and require a suitable diet. A diet that is high in good-quality animal protein and fat and low in complex carbohydrates and fiber is recommended. Ferrets are routinely immunized against canine distemper virus (CDV) and rabies virus. Ferrets are quite susceptible to CDV, and there is a 100% mortality rate in unvaccinated ferrets infected with CDV. When a new ferret is brought into the household, a quarantine period is recommended before introducing it to other animals, particularly other ferrets. The purpose of the quarantine period is to identify and prevent transmission of infectious disease potentially carried by the new ferret. The duration of this period allows for the development of any clinical signs in a seemingly healthy ferret following entrance into the new household.